Both high and low dispersal? Apparently contradictory genetic patterns in the Antarctic littorinid gastropod Laevilacunaria antarctica - González-Wevar, Claudio A.; Poveda, Yarleth; Segovia, Nicolás I.; Rosenfeld, Sebastián; Maturana, Claudia S.; Jeldres, Vanessa; Schmider-Martínez, Andreas; Gérard, Karin; Spencer, Hamish G.; Poulin, Elie (Frontiers in Ecology and Evolution, 2024)
How the near-shore marine benthic communities survived Quaternary glaciations in Antarctica is a major question for Southern Ocean biogeographers. Several hypotheses that consider life-history traits, such as bathymetric ranges and developmental modes, have been proposed. Near-shore species with high dispersive potential are expected to show star-like genealogies, with broadly distributed haplotypes surrounded by closely related variants at low frequencies, a consequence of rapid population post-glacial expansion mediated by larvae. By contrast, shallow-water taxa with low dispersal potential are expected to evidence marked genetic structure or even consist of separate cryptic species, due to their survival in small refugial populations subject to repeated bottlenecks.In this study we performed phylogeographic analyses on the high-latitude littorinid Laevilacunaria antarctica across its distribution from maritime Antarctica to South Georgia. This species is a highly abundant near-shore gastropod, commonly found on macroalgae, with low autonomous vagility and exhibits benthic protected development with no free-living dispersive stages. Such characteristics make this species a suitable model to test the above hypotheses. Contrary to low dispersal potential predictions, L. antarctica comprises a single unstructured unit across its distribution in maritime Antarctica, exhibiting a typical high-dispersal star-like, shortbranched genealogy centered on a dominant broadly distributed haplotype. The South Georgia population, however, consists of a separate genetic unit, strongly differentiated from those of the maritime Antarctic. We estimate that these two genetic groups separated 1.2 My, long before the Last Glacial Maximum and evolved independently in these areas. Our results thus provide partial support for the expected pattern for a near-shore marine benthic species with low innate dispersive potential.On a wider geographic scale (maritime Antarctica vs South Georgia), our results in L. antarctica provide support for the expected pattern for a near-shore marine benthic species with low innate dispersive potential. However, on a narrower scale (maritime Antarctica) life-history characters including the close association of the species with macroalgae, would allow dispersal and a species with low dispersal potential exhibits paradoxically an absence of genetic structure across hundreds of kilometers probably mediated by rafting.